2017
DOI: 10.3389/fmicb.2017.01608
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal Influence of Ionic Liquids on Phages P100 and MS2

Abstract: An increasing number of publications describe the potential of ionic liquids (ILs) as novel antimicrobials, antibacterial coatings and even as active pharmaceutical ingredients. Nevertheless, a major research area, notably their impact on viruses, has so far been neglected. Consequently the aim of this study was to examine the effects of ILs on the infectivity of viruses. A systematic analysis to investigate the effects of defined structural elements of ILs on virus activity was performed using 55 ILs. All str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 53 publications
5
31
0
Order By: Relevance
“…The mechanism of (cyto) toxicology of ILs has still remained unclear. Jing et al [ 187 , 188 ], have investigated the interaction of ILs possessing amphiphilic characteristics with a lipid bilayer as a model cell membrane to examine cytotoxicity at a molecular level. By the use of fluorescence imaging and light and X-ray scattering, they have found that ILs disrupt the lipid bilayer by insertion of IL, end-capping the hydrophobic edge of the lipid bilayer.…”
Section: Usefulness Of Ionic Liquids In Medicinementioning
confidence: 99%
“…The mechanism of (cyto) toxicology of ILs has still remained unclear. Jing et al [ 187 , 188 ], have investigated the interaction of ILs possessing amphiphilic characteristics with a lipid bilayer as a model cell membrane to examine cytotoxicity at a molecular level. By the use of fluorescence imaging and light and X-ray scattering, they have found that ILs disrupt the lipid bilayer by insertion of IL, end-capping the hydrophobic edge of the lipid bilayer.…”
Section: Usefulness Of Ionic Liquids In Medicinementioning
confidence: 99%
“…Restrictions on the use of agents as standards for decontamination also result from inactivity against viruses, especially those transmitted in surgical wards [ 51 ]. Difficulties in combating viruses were associated with massive hepatitis B and C virus infection outbreaks (HBV, HCV) in the 1980′s and 1990′s of the 20th century [ 53 ]. In neonatal wards, the main problems are contact viruses, such as influenza virus, rotavirus, and norovirus [ 51 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties in combating viruses were associated with massive hepatitis B and C virus infection outbreaks (HBV, HCV) in the 1980′s and 1990′s of the 20th century [ 53 ]. In neonatal wards, the main problems are contact viruses, such as influenza virus, rotavirus, and norovirus [ 51 , 53 ]. ILs also show antiviral activity in addition to antibacterial activity [ 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations